The larva of Sericostoma galeatum Rambur 1842 (Trichoptera: Sericostomatidae), based on French material - Waringer, Johann; Coppa, Gennaro (Zootaxa, 2021)
The present paper describes the previously unknown larva of Sericostoma galeatum based on French material. Information on the morphology of the larva is given, and the most important morphological characters are illustrated. Sericostoma galeatum is very close to the S. personatum / S. flavicorne species pair and cannot be separated yet from those confusing congeners. With respect to the distribution, S. galeatum is confined to the French, Italian, and Swiss western Alps and the Apennines. In addition, ecological information is provided.